Meningkatkan Aktivitas dan Hasil Belajar Siswa Melalui Pembelajaran Kooperatif Model Numbered Head Together dalam Reading Text di Kelas XII IPS 2 pada SMAN 12 Banjarmasin Tahun Pelajaran 2016/2017 - Ronny ralin (Jurnal PTK dan Pendidikan, 2018)
Numbered Head Together can enhance cooperation among students. Cooperative learning model Numbered Head Together can improve student’s activity and learning outcomes in reading text Class XII IPS 2 at SMAN 12 Banjarmasin Lesson Year 2016/2017. The activity of students during the learning changes in cycle I is the most is enough student activity from 37 students there are 21 students (56.76%) whereas in cycle II the activity is not enough and the most excellent student activity is 27 students (72, 97%). Student learning outcomes in the complete cycle I amounted to 26 students (70.3%) increased to 34 students (91.9%), while the non-completeness of students decreased in the first cycle there